Effects of vibration training on motor and non-motor symptoms for patients with multiple sclerosis: A systematic review and meta-analysis - Zhang, Yang; Xu, Peng; Deng, Yu; Duan, Wenxiu; Cui, Juncai; Ni, Chaomin; Wu, Ming (Frontiers in Aging Neuroscience, 2022)
Background: Vibration therapy is one of the rehabilitation programs that may be effective in treating both motor and non-motor symptoms in Multiple Sclerosis patients. We conducted a comprehensive systematic review and meta-analysis to assess the effects of vibration therapy on motor and non-motor symptoms (functional mobility, balance, walking endurance, gait speed, fatigue, and quality of life) of this population. Methods: A systematic search of PubMed, Embase, the Cochrane Library, Web of Science, Physiotherapy Evidence Database, Scopus, Google Search Engine, and the China National Knowledge Infrastructure (CNKI). Two reviewers independently assessed the study quality. Results: Fourteen studies with 393 participants were finally included in the meta-analysis. The pooled results showed that vibration therapy had a significant advantage over the control intervention in improving balance function (mean difference [MD] = 2.04, 95% confidence interval [CI]: 0.24 – 3.84,P = 0.03), and walking endurance (SMD = 0.34, 95% CI: 0.07–0.61,P = 0.01. Meanwhile, the degree of disability subgroup analysis revealed that the Expanded Disability Status Scale (EDSS) score (3.5-6) significantly improved functional mobility (MD: -1.18, 95% CI: -2.09–0.28, P =0.01) and balance function (MD: 3.04, 95% CI: 0.49–5.59, P =0.02) compared with the control group, and the EDSS (0-3.5) were more beneficial in walking endurance. The duration subgroup analysis indicated a significant difference in the effect of the duration (< 4 weeks) on enhancing walking endurance (SMD:0.46, 95% CI: 0.04–0.87, P =0.03). However, no significant improvement was found in functional mobility, gait speed, fatigue, and quality of life. Conclusion: Vibration therapy may improve balance function and walking endurance, and the degree of disability and duration of intervention may affect outcomes. The evidence for the effects of vibration therapy on functional mobility, gait speed, fatigue, and quality of life remains unclear. More trials with rigorous study designs and a larger sample size are necessary to provide this evidence.